People under power: early Jewish and Christian responses to the Roman Empire - Labahn, Michael; Lehtipuu, Outi (Early Christianity in the Roman world, 2015)
Cover -- Contents -- Introduction -- Christians, Jews, and Roman Power -- Outi Lehtipuu & Michael Labahn -- Part I -- Jewish Communities in the Shadows of the Empire -- The Kittim and Hints of Hybridity in the Dead Sea Scrolls -- George J. Brooke, University of Manchester -- The Politics of Exclusion -- Expulsions of Jews and Others from Rome -- Birgit van der Lans, University of Groningen -- Μεμορια Iudati patiri -- Some Notes to the Study of the Beginnings of Jewish Presence in Roman Pannonia -- Nóra Dávid, University of Vienna -- Part II -- Contextualizing New Testament Texts with the Empire -- Imperial Politics in Paul -- Scholarly Phantom or Actual Textual Phenomenon-- Anders Klostergaard Petersen, University of Aarhus -- Das Markusevangelium -- eine ideologie- und imperiumskritische Schrift-- Ein Blick in die Auslegungsgeschichte -- Martin Meiser, Universität des Saarlandes -- "Ein Beispiel habe ich euch gegeben ..." (Joh 13,15) -- Die Diakonie Jesu und die Diakonie der Christen in der johanneischen Fußwaschungserzählung als Konterkarierung römischer Alltagskultur* -- Klaus Scholtissek, Friedrich-Schiller-Universität Jena -- Part III -- Imperial Ideology and Other Early Christian Texts -- The Shepherd of Hermas and the Roman Empire -- Mark R.C. Grundeken, Catholic University of Leuven -- Noble Death or Death Cult-- Pagan Criticism of Early Christian Martyrdom -- Paul Middleton, University of Chester -- Nero Redivivus as a Subject of Early Christian Arcane Teaching -- Marco Frenschkowski, University of Leipzig -- A Selection of Ancient Sources.